2011
DOI: 10.1007/s12028-011-9502-2
|View full text |Cite
|
Sign up to set email alerts
|

Electric Versus Manual Tooth Brushing among Neuroscience ICU Patients: Is it Safe?

Abstract: Background: Poor oral hygiene has been associated with ventilator-acquired

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
11
0
5
Order By: Relevance
“…The remaining eight were retrieved for full text review, and four of them were excluded because one did not report outcomes of interest [16], one pertained to electric rather than manual toothbrushing [17], one was currently ongoing [18], and one was duplicated data [19]. Thus, four RCTs were included in the final analysis [20-23].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining eight were retrieved for full text review, and four of them were excluded because one did not report outcomes of interest [16], one pertained to electric rather than manual toothbrushing [17], one was currently ongoing [18], and one was duplicated data [19]. Thus, four RCTs were included in the final analysis [20-23].…”
Section: Resultsmentioning
confidence: 99%
“…One report was translated from Spanish to English to evaluate eligibility (37). Of 14 potentially eligible studies, we excluded one Low risk of bias High study of toothbrushing which did not randomize patients (45); two studies that started as randomized trials but which became observationalstudies following low enrolment (46) or apparently large treatment effect (47), neither of which reported numerators or denominators; two trials that reported dental plaque but not VAP and that focused on the outcome of intracranial pressure (48,49); and three trials using toothbrushing as part of a standard oral care protocol in both groups testing chlorhexidine vs. control (50,51) or chlorhexidine vs. bicarbonate vs. control (52). Agreement on trial selection was 100%.…”
Section: Trial Identificationmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] In contrast, administration of oral care by using either manual or electric toothbrushes among intubated neurologically impaired patients does not result in significant increases in ICP. 18,19 Similarly, Olson et al, in a series of 3 articles, 5,20,21 explored the effects of chest percussion therapy on ICP, finding that such therapy does not adversely affect ICP and may be associated with lower ICP for some patients. Although these interventions are often necessary to provide adequate care for critically ill patients, as they reduce risk of ventilatorassociated pneumonia and pressure ulcers, other nursing interventions are performed with the aim of specifically decreasing ICP values.…”
Section: Review Of Literaturementioning
confidence: 99%